On the huntsman spider genus Vindullus Simon, 1880 (Araneae: Sparassidae) - Rheims, Cristina Anne (Zootaxa, 2019)
Vindullus Simon, 1880 is revisited and two species, erroneously allocated in Olios Walckenaer, 1837, are transferred to the genus. Vindullus fugiens (O. Pickard-Cambridge, 1890) comb. nov. and V. guatemalensis (Keyserling, 1887) comb. nov. were described based on male specimens from Guatemala. Both species are redescribed and illustrated. A revised diagnosis is given for the genus including newly evaluated characters for freshly collected females of V. angulatus Rheims & Jäger, 2008. In addition, an illustrated identification key for all known males of the genus is provided, new distribution records are listed for V. angulatus Rheims & Jäger, 2008, V. gibbosus Rheims & Jäger, 2008 and V. gracilipes (Taczonowski, 1872) and a distribution map is provided showing the updated distribution of the genus.